Endocytic trafficking of cholera toxin in Balb 3T3 cells - Blagojević Zagorac, Gordana; Mahmutefendić Lučin, Hana; Kučić, Natalia; Ilić Tomaš, Maja; Lučin, Pero (2008)
Summary: Endocytosis of the cholera toxin B subunit (CTxB) in various cell lines has shown diversity of entry paths of cell surface bound ligands. The aim of this study was to clarify internalisation mechanism and endosomal trafficking of CTxB in murine fibroblasts (Balb 3T3 cells) and human epithelial cells (HeLa). We have shown that CTxB enters Balb 3T3 cells mainly via cholesterol-dependent endocytic pathway(s), while in HeLa cells clathrin endocytosis plays a major role. Early endosomal acidic gradient is required for CTxB progression towards the Golgi in HeLa cells, whereas a majority of internalised CTxB bypasses early endosomes (EEA1+ compartments) in Balb 3T3 cells. The acidic gradient is also required for exit from the Golgi into the late endosomes and degradation of CTxB in Balb 3T3 cells. Thus, the CTxB trafficking may help in the understanding of non-clathrin endocytic mechanisms and the complexity of late endosomal compartments
Bibliografija: 55 jed
Sažetak
Keywords: Toksini kolere -- Fibroblasti -- Epitelne stanice -- Endocitoza